2018
DOI: 10.1038/s41438-018-0020-7
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in the transcriptional landscape between low temperature and freeze shock in cultivated grapevine (Vitis vinifera)

Abstract: Low-temperature stresses limit the sustainability and productivity of grapevines when early spring frosts damage young grapevine leaves. Spring conditions often expose grapevines to low, but not damaging, chilling temperatures and these temperatures have been shown to increase freeze resistance in other model systems. In this study, we examined whole-transcriptome gene expression patterns of young leaf tissue from cuttings of five different grapevine cultivars, exposed to chill and freeze shock, in order to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 58 publications
1
55
0
Order By: Relevance
“…The pathways associated with starch and sugar metabolism were signi cantly enriched. Cold treatment also seemed to trigger enzymes responsible for the production of amylose, starch, maltose, and dextrin [35]. A few key changes in gene expression suggested that these pathways were utilized differently between F 1 populations with different cold tolerances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathways associated with starch and sugar metabolism were signi cantly enriched. Cold treatment also seemed to trigger enzymes responsible for the production of amylose, starch, maltose, and dextrin [35]. A few key changes in gene expression suggested that these pathways were utilized differently between F 1 populations with different cold tolerances.…”
Section: Discussionmentioning
confidence: 99%
“…Plants have evolved sophisticated strategies in which hormone and cold signaling pathways are coordinated to better adapt to freezing stress. Ethylene insensitive 3 (EIN3) is a key transcription factor involved in ethylene signaling that negatively regulates freezing tolerance in Arabidopsis, partially by affecting the expression of CBFs by binding to the EBS motifs in their promoters [35,43]. Two F-box proteins, EIN3-binding F-box 1/2 (EBF1/2), positively regulate CBF expression by mediating the degradation of EIN3 and PIF3 via the 26S proteasome pathway [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Expression data of grapevine genes co‐expressed under normal and cold/low‐temperature treatments was retrieved from Londo et al . (). Similarly, the expression of A. thaliana co‐expressed genes was retrieved via the Bio‐Analytic Resource (BAR, http://bar.utoronto.ca/) expression browser tool from the ‘AtGenExpress – Stress series’ and ‘Cold stress’ option.…”
Section: Methodsmentioning
confidence: 97%
“…The RNA-seq data of overexpression plants can present new insights into the regulation network of many genes [6,9,10]. A comparison of the RNA-seq datasets of plants under different abiotic or biotic stresses can yield candidate genes related to these stresses [5,[11][12][13]. Breeders can explore the inherent rules of plant breeding and cultivation according to the expression status of the RNA-seq in different plants or areas [14].…”
Section: Introductionmentioning
confidence: 99%